2016
DOI: 10.3389/fpsyg.2016.01972
|View full text |Cite
|
Sign up to set email alerts
|

Need for Affiliation as a Motivational Add-On for Leadership Behaviors and Managerial Success

Abstract: In a sample of 70 leader-follower dyads, this study examines the separate and interactive effects of the leaders’ implicit needs for power, achievement, and affiliation on leadership behaviors and outcomes. Results show that whereas the need for achievement was marginally associated with follower-rated passive leadership, the need for affiliation was significantly related to ratings of the leaders’ concern for the needs of their followers. Analyzing motive combinations in terms of interactive effects and accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 89 publications
(194 reference statements)
0
24
0
2
Order By: Relevance
“…Because some studies already linked higher scores on implicit achievement to higher salaries (Cummin, 1967;Seibert & Kraimer, 2001), we also expect the implicit achievement motive to be positively related to income. Specifically, people high in the implicit achievement motive prefer work settings in which they can ask for frequent feedback on their performance levels, in order to optimize their performance (Steinmann, Ötting, & Maier, 2016). Finally, a few studies also suggested implicit power to be positively related to objective career success and income levels (Cummin, 1967;Steinmann, Dörr, Schultheiss, & Maier, 2015).…”
Section: Traits Motives and Income Levels At The Starting Point Of mentioning
confidence: 99%
See 3 more Smart Citations
“…Because some studies already linked higher scores on implicit achievement to higher salaries (Cummin, 1967;Seibert & Kraimer, 2001), we also expect the implicit achievement motive to be positively related to income. Specifically, people high in the implicit achievement motive prefer work settings in which they can ask for frequent feedback on their performance levels, in order to optimize their performance (Steinmann, Ötting, & Maier, 2016). Finally, a few studies also suggested implicit power to be positively related to objective career success and income levels (Cummin, 1967;Steinmann, Dörr, Schultheiss, & Maier, 2015).…”
Section: Traits Motives and Income Levels At The Starting Point Of mentioning
confidence: 99%
“…Highly power-oriented people might be better at negotiating salaries because of a large focus on status, elevated levels of confidence, and higher likelihood of using manipulative behaviors (Trapp & Kehr, 2016). Implicit power motive is also linked to networking behaviors and employees' increased visibility in organizations (Steinmann et al, 2016), which has been related to higher income levels. Based on the above-mentioned literature on implicit motives, we hypothesized:…”
Section: Traits Motives and Income Levels At The Starting Point Of mentioning
confidence: 99%
See 2 more Smart Citations
“…A study investigated 416 registered nurses in Finland, and results showed that higher perceived structural empowerment by nurses can improve their self-determination (Kuokkanen, Leino-Kilpi, & Katajisto, 2003). Related research showed that empowerment plays an irreplaceable role in the stage of career development (Steinmann, Ötting, & Maier, 2016). Kanter (1982) emphasizes that employees with organizational structures of power and opportunity can achieve career goals as well as improve organizational production.…”
Section: Structural Empowerment Innovative Behaviour and Career Smentioning
confidence: 99%